Clinical and morphological features of combined hyperplastic diseases of the uterus against the background of adenomyosis - N. M. Rozhkovskaya; V. O. Sitnikova; S. M. Sivyi; I. S. Lomakina (Kazimierz Wielki University, 2020)
To determine clinical and morphological features of combined uterine hyperplastic diseases in premenopausal women at the background of adenomyosis, 62 patients operated on for chronic abnormal uterine bleeding were examined. The control group consisted of 30 premenopausal patients who applied for preventive examination. Anthropometric and ultrasound examinations, assessment of carbohydrate and lipid metabolism, histologic examination were done. It has been established that uterine hyperplasia patients often had lipid metabolism damages (dislipidemy) and damages of carbohydrate one (alimentary - constitutional obesity, metabolic syndrome) which worsen the clinical course of the main disease. According to histological examination data, the activity of adenomyosis foci in patients with comorbid uterine pathology correlated with the severity of clinical manifestations (abnormal uterine bleeding, pain) and the presence of comorbid lesions (concomitant endometrial hyperplasia, chronic endometriosis, fibroids, endometriosis).